PENGARUH MODEL PEMBELAJARAN ROLE PLAYING TERHADAP KETERAMPILAN BERBICARA SISWA PADA MATA PELAJARAN BAHASA INDONESIA DI KELAS V SD - Rian Natanael; Widya Handayani; Amiruddin (STKIP Subang, 2026)
The purpose of this study is to examine the impact of the role-playing learning model on the oral communication skills of Indonesian language students enrolled in the fifth grade at SD Negeri 63 Palembang. “There was a posttest-only control group in this quasi-experimental investigation. Eleven students from the experimental group and nineteen from the control group made up the sample size of thirty-seven. Oral tests and documentation were used to gather data. Utilizing IBM SPSS Statistics version 26, we performed data analysis utilizing tests for normality and homogeneity as well as Independent Sample t-tests. The experimental group averaged 79.1 on the speaking ability test, whereas the control group averaged 52.8.” The results of the hypothesis test demonstrated that the Role Playing learning model significantly impacted students' speaking abilities, as the t-value (9.900) exceeded the t-table value (2.030) with a significance value of 0.000 <0.05.